BLOOD AND ACID-BASE CHANGES IN CAILVES EICPERIMENTALLY INFECTED WITH SALMONELLA TYPHIMPRIUM - Habasha, F.G.; Michael , K,; Al-Jebouril, K.O. (The Iraqi Journal of Veterinary Medicine, 2022)
The experimental design of this study was included (12) Friesian calves aged between 3-5 weeks. Calves were divided into two groups. Group I consisted of (8) calves were infected experimentally with 1.5 x 10“ of Salmonella typhimurium and often that treatment with chloramphenicol and electrolytes ﬂuid were takes place. Group II consisted of (4) calves were infected with organisms but without treatment. The clinical ﬁndings of the disease were characterized by two forms which includes the septicemic and enteric forms. Haematological changes revealed a variable number of the total and differential leukocytic count, increased PCV, ﬁbnnogen and decreased of the total plasma protein. . The changes in the acid-based balance indicate the development of metabolic acidosis.